Enhancement of femtosecond laser-induced nucleation of protein in a gel solution - Murai, Ryota; Yoshikawa, Hiroshi; Takahashi, Yoshinori; Maruyama, Mihoko; Sugiyama, Shigeru; Sazaki, Gen; Adachi, Hiroaki; Takano, Kazufumi; Matsumura, Hiroyoshi; Murakami, Satoshi; Inoue, Tsuyoshi; Mori, Yusuke (Applied physics letters, 2010)
We found that the use of a gel solution with agarose enhanced femtosecond laser-induced nucleation and produced hen egg white lysozyme crystals at three to five times lower supersaturation than those by the femtosecond laser or agarose alone. The fast fluorescence imaging of the protein in the gel solution revealed that cavitation bubbles created high-concentration regions at the focal point, which could be the trigger for protein nucleation. The lower diffusions of protein molecules in agarose gel retained the high-concentration regions for a longer time, and facilitated the nucleation.
Gesehen am 17.05.2023